Personalized individual-based exercise prescriptions are effective in treating depressive symptoms of college students during the COVID-19: A randomized controlled trial in China - Zhao, Yuanhui; Wang, Wenxing; Wang, Mengdie; Gao, Fang; Hu, Chun; Cui, Bowen; Yu, Wenlang; Ren, Hong (Frontiers in Psychiatry, 2023)
Background The COVID-19 pandemic has seriously increased depression prevalence among the public, including Chinese college students. However, many exercise cannot be performed as usual under the stay-at-home order. This study was a 12-week three-arm randomized controlled trial using the intention-to-treat principle, aiming to explore and compare the feasibility and effect of individual-based personalized aerobic-exercise and resistance-training prescriptions on depressive symptoms in college students, and conclude with some recommendations for individual-based exercise prescriptions. Methods Eighty-six college students with depressive symptoms were randomized into aerobic-exercise (AE), resistance-training (RT), and wait-list control (WLC) groups. Participants in two experimental groups received 12-week personalized AE and RT prescriptions on their individual situations, respectively. No intervention was implemented on participants in the WLC group. Depressive symptoms and physical activity (PA) were measured by Zung Self-Rating Depression Scale (SDS) and International Physical Activity Questionnaire-Short Form (IPAQ-SF), respectively. All data were collected at the baseline, 4, 8, and 12 weeks, and 4-week post-intervention. Results At 12 weeks, 72.09% of depressive participants improved to “normal.” Participants exhibited a statistical reduction in SDS in all 3 groups (p < 0.05) at 12 weeks compared to baseline. Follow-up assessments showed no significant increase in SDS at 4-week post-intervention compared to 12 weeks (p > 0.05). The independent t-test revealed significantly lower SDS in AE and RT group than in WLC group (pAE < 0.001 and pRT < 0.05) at 4, 8, and 12 weeks, and 4-week post-intervention. Furthermore, the PA of participants (including total PA and intensities) in both experimental groups represented a significant improvement at 4-week post-intervention compared to baseline (p < 0.05), while no differences were observed in the PA of participants in the WLC group (p > 0.05). Conclusion Personalized exercise prescriptions have good feasibility as they can increase adherence to intervention and reduce serious adverse events. Besides, individual-based personalized aerobic-exercise and resistance-training prescriptions result in a similar effect in relieving depressive symptoms and improving physical activity in college students. The individual-based exercise programs performed in 45- to 60- min with progressive moderate-to-vigorous intensity, 3 times/week for at least 12 weeks, may reduce depressive symptoms in college students during the COVID-19.